Kenya : Technical Assistance Report-Monetary and Financial Statistics Mission (December 3-14, 2018). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
This technical assistance report on Kenya reviews the implementation of the recommendations made by the monetary and financial statistics (MFS) mission in January 2017 and the expanded coverage of the standardized report form for other depository corporations (SRF 2SR) including savings and credit cooperatives (SACCOs), microfinance banks (MFBs), and money market funds. The mission found that the Central Bank of Kenya (CBK) had made significant progress in collaborating with other financial sector regulatory authorities by forming the Technical Working Group and holding regular meetings. The previous missions recommended that the CBK improve coordination with other regulatory authorities to cooperate and collaborate on the compilation of MFS. With source data available for deposit taking SACCOs and MFBs, the CBK made significant progress in producing initial provisional data for 2SR with the coverage expanded to include those data which were reported to IMF's Statistics Department for review in August of 2017. In order to support progress in the various work areas, the mission recommended a detailed action plan with the different priority recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet